EPID-26. ALIGNING THE CBTRUS HISTOLOGY GROUPS WITH 2016 WHO CLASSIFICATION OF TUMORS OF THE CENTRAL NERVOUS SYSTEM. (12th November 2021) - Kruchko, Carol; Patil, Nirav; Cioffi, Gino; Brat, Daniel; Bruner, Janet; McLendon, Roger; Tihan, Tarik; Barnholtz-Sloan, Jill; Ostrom, Quinn
Abstract: BACKGROUND: The Central Brain Tumor Registry of the United States (CBTRUS) uses a histology grouping scheme modeled after the World Health Organization (WHO) Classification of Tumours of the Central Nervous System (CNS) to classify cancer registry records for clinically relevant statistical reporting. Molecular studies have identified genetic features which precisely stratify tumor types, resulting in the 2016 update to the WHO Classification incorporating these markers. To continue providing clinically relevant statistics, the histology groupings have been aligned with the 2016 update. Resulting changes to groupings were assessed. METHODS: In collaboration with four consulting neuropathologists the scheme was reviewed and realigned to the 2016 update. Obsolete histology nomenclature and ICD-O-3 codes were identified. Evaluation of the frequency of affected codes in the 2013-2017 data was conducted. RESULTS: 417, 767 total cases of primary brain and CNS tumors were diagnosed during 2013-2017 in the US. After review of the CBTRUS grouping scheme, 67 codes were noted to be obsolete, 51 codes were re-classified and 12 new codes were incorporated. This reorganization could result in grouping assignment or reporting changes for 2, 588 cases (0.6%). The histology groups most significantly affected were mesenchymal tumors and neuronal and mixed neuronal glial tumors. CONCLUSIONS: The 2016 revision to WHO Classification has affected collection and reporting of CNS tumors. The CBTRUS data edits program is now undergoing revision, which will become the basis of reporting. Some histology-specific molecular markers require additional data to distinguish between cases. In collaboration with CBTRUS, the NAACCR SSDI Committee developed a new variable for collection of molecular information. This variable was included in Uniform Data Standards beginning on January 1, 2018 and will be available for reporting in 2021. A 2021 update to the WHO Classification is scheduled for release later this year, requiring further classification updates.